1990
DOI: 10.2105/ajph.80.9.1091
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis transmission among the Sioux Indians of South Dakota.

Abstract: Hepatitis A continues to occur in cyclical communitywide epidemics on the Indian reservations of South Dakota. In June 1985 a population-based serosurvey for viral hepatitis involving 120 households was conducted at the Pine Ridge and Rosebud Sioux Indian reservations in South Dakota. The serosurvey was performed shortly after a large hepatitis A epidemic on the Pine Ridge reservation in 1983-84, and immediately before a large hepatitis A epidemic on the Rosebud reservation in 1985-86. The overall seroprevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
2
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 17 publications
0
17
2
2
Order By: Relevance
“…7-10 Toddlers often have asymptomatic infection and are the source of silent transmission to susceptible persons and maintenance of the virus in a community over time. 3 Therefore, sustained vaccination of children, preferably as part of the early childhood immunization schedule, will be required to prevent HAV transmission and the reintroduction of disease into communities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7-10 Toddlers often have asymptomatic infection and are the source of silent transmission to susceptible persons and maintenance of the virus in a community over time. 3 Therefore, sustained vaccination of children, preferably as part of the early childhood immunization schedule, will be required to prevent HAV transmission and the reintroduction of disease into communities.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic studies in this and neighboring populations showed a high prevalence of hepatitis A virus (HAV) infection among adults. 3 Eligible participants were infants born to mothers who received well-child care at the Rapid City Indian Health Service (Sioux San) Hospital. Infants were excluded if they received IG, immunosuppressive therapy, blood, or blood products; were immune-compromised; were born to hepatitis B surface antigen-positive mothers; or were diagnosed with a severe developmental disability or progressive or unstable neurologic disorder.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, the incidence of chronic active hepatitis was 193 per 100,000 in men, and that of cirrhosis 107 per 100,000 over 7815 carrier-years [50]. Research examining prevalence in mainland Native Americans is scant, with little data on natural history or treatment outcomes [51].…”
Section: Alaska Nativesmentioning
confidence: 99%